Structural Suitability Assessment of Factory Building PT. Suka Sari Mitra Mandiri Semarang Regency - Prabowo, Rizal Agung; Antonius, Antonius; Setiyawan, Prabowo (TEKNIK, 2025)
Assessment and repairs must be carried out if a structure experiences a decrease in structural strength. To restore the performance of the structure and extend the service life of a building structure that has experienced degradation due to damage to some of its structural components, mitigation measures are needed. The purpose of this study was to determine the safety and feasibility of PT's building structure. Suka Sari Mitra Mandiri, Semarang Regency. The analysis method used was to compare the feasibility of the building and building safety with applicable reference standards such as SNI and PermenPU. The results of the analysis that have been carried out obtained the condition of the PT. Suka Sari Mitra Mandiri Building in a safe and prime condition. So it can be concluded that the PT. Suka Sari Mitra Mandiri Building Structure is declared structurally feasible and safe